PENGARUH PENGGUNAAN MEDIA MANIPULATIF TERHADAP HASIL BELAJAR MATEMATIKA KELAS IV SEKOLAH DASAR - Rosita Rosita; Budiman Tampubolon; Tahmid Sabri (Universitas Tanjungpura, 2019)
AbstractThe problem in this research was the influence by using manipulaitve media in Matematic Learning against the results of the grade IV elementary school number 05 Pontianak city. The method used was the experiment with forms of Experimental Design Quaisy design non equivalent control group design. This research sample was grade IV A of as a class experiment and grade IV B of as a class control. Data collection techniques used are measurement techniques and data-collecting instrument was the written test multiple choice-shaped. Based on the analysis of data obtained average results post-test experiments class with an average 75,17 and post-test control class 67,04. Hypothesis test results using t-test (Polled Variance) obtained = 2.566 while for dk (23+23 - 2 = 44) with significant level α = 5% obtained = 1.681, meaning >, then the Ha received, this proves there was influence by using manipulative media in matematic learning. Based on the results of the calculation of effect size (ES) obtained ES = 0.79 which included the criteria of medium. Therefore it can be concluded that using manipulative media in matematic learning provide positive influence towards learning outcomes grade IV elementary school number 05 Pontianak city. Keyword: Influence, Manipulative Media, TheResults of the Matematic Learning